Comparative power demand of mechanical and aeration imposed shear in an immersed membrane bioreactor. (1st December 2017) - Buzatu, P.; Qiblawey, H.; Nasser, M.S.; Judd, S.
Abstract: The power demanded for the application of mechanically-imposed shear on an immersed flat sheet (iFS) membrane bioreactor (MBR) has been compared to that of conventional membrane air scouring. Literature correlations based on the Ostwald model were used to define the rheological characteristics of an MBR sludge. The correlation of specific power demand ( P ' ¯, in Watts per m 2 membrane area) with shear rate γ in s −1 was developed from first principles through a consideration of the force balance on the system in the case of mechanically-imposed shear. The corresponding aeration imposed shear correlation was interpreted from literature information. The analysis revealed the energy required to impose a shear mechanically through oscillation (or reciprocation) of the membrane to be between 20 and 70% less than that demanded for providing the same shear by conventional aeration of the immersed membrane. The energy saving increases with decreasing shear in accordance with a power demand ratio (aeration:mechanical) of 1400 γ −1.4 for a specific sludge rheology. Whilst the absolute P ' ¯ value is dependent on the sludge rheology, the aeration:mechanical power demand ratio is determined by the difference in the two exponents in the respective correlations between P ' ¯ and γ . Consequently, aeration-imparted shear becomes energetically favoured beyond some threshold shear rate value (∼180 s −1, based on the boundary conditions applied in the current study). The outcomes qualitatively corroborate findings from the limited practical measurement of energy demand in MBRs fitted with reciprocating immersed membranes. Graphical abstract: Image Highlights: Mechanical and aeration-imposed shear in an immersed membrane bioreactor compared. Sludge rheology encompassed using literature viscosity ( η ) vs shear ( γ ) relationships. Specific power demand determined as a function of γ for both systems. Power demand for mechanical shear 20–70% less than that of conventional air scouring. Absolute power demand strongly dependent on sludge rheological properties (η vs. γ).